Desain dan Perancangan Aplikasi Pemantauan Pencegahan Stunting untuk Balita - Muslih, Muslih; Pramudya, Elkaf Rahmawan; Muqoddas, Ali; Hasyim, Noor; Senoprabowo, Abi; asfawi, Supriyono (Jurnal SITECH : Sistem Informasi dan Teknologi, 2024)
Stunting, a growth disorder caused by malnutrition, has a long-term impact on children's health and development. Pemantauan the development of physical parameters such as height, weight, head circumference and upper arm circumference, as well as changes in growth patterns, is an effective method for early detection of stunting. These measurements help identify stunted growth or signs of nutritional deficiencies. Integrated data collection and pemantauan applications play an important role in optimizing this process. Data recording is more accurate and has historical records that allow for analysis of child growth. Using the data obtained, health service providers such as posyuandu can identify children at risk of stunting and respond with appropriate actions. data collection applications can increase the involvement of parents and community members by providing easily accessible and useful information related to children's health. This supports prevention efforts and encourages communication between families, health workers and related institutions. This effort not only contributes to the health of individual children but also plays a role in improving the health of society as a whole through a prevention approach based on data obtained and integrated between parts of society.